2020
DOI: 10.1371/journal.pone.0235442
|View full text |Cite
|
Sign up to set email alerts
|

Identification of characteristic compounds of moderate volatility in breast cancer cell lines

Abstract: In this study, we were challenging to identify characteristic compounds in breast cancer cell lines. GC analysis of extracts from the culture media of breast cancer cell lines (MCF-7, SK-BR-3, and YMB-1) using a solid-phase Porapak Q extraction revealed that two compounds of moderate volatility, 1-hexadecanol and 5-(Z)-dodecenoic acid, were detected with markedly higher amount than those in the medium of fibroblast cell line (KMST-6). Furthermore, LC-TOF/MS analysis of the extracts clarified that in addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
5
1
2
Order By: Relevance
“…En los diferentes estudios se ha reconocido que las células transformadas inducen una reprogramación metabólica en la búsqueda y generación de energía que derivan de la glucólisis aeróbica y la oxidación de ácidos grasos de cadena media y larga, lo cual implica que se aleje de la vía de la fosforilación oxidativa mitocondrial o efecto Warburg 31 . Esto se explica mediante la exposición a microambientes con estrés oxidativo 18 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En los diferentes estudios se ha reconocido que las células transformadas inducen una reprogramación metabólica en la búsqueda y generación de energía que derivan de la glucólisis aeróbica y la oxidación de ácidos grasos de cadena media y larga, lo cual implica que se aleje de la vía de la fosforilación oxidativa mitocondrial o efecto Warburg 31 . Esto se explica mediante la exposición a microambientes con estrés oxidativo 18 .…”
Section: Discussionunclassified
“…De los análisis de COV provenientes de líneas celulares, se identificaron cinco estudios basados en la experimentación in vitro de líneas celulares y biopsia de tejido mamario maligno. En cuatro estudios se empleó la línea celular MCF-7 [16][17][18][19] , en dos estudios utilizaron las células MDA-MB-231 [17][18][19] y en un estudio utilizaron biopsias de tejido mamario maligno 20 . Como resultado, se obtuvieron 72 COV agrupados en su mayoría en alcoholes, cetonas, alcanos y aldehídos (Fig.…”
Section: Evidencia In Vitro De Que Las Líneas Celulares «Exhalan» Covunclassified
“…In different studies, it has been recognized that transformed cells induce metabolic reprogramming in the search for and generation of energy deriving from aerobic glycolysis and medium and long chain fatty acids oxidation, which implies that it moves away from the pathway of mitochondrial oxidative phosphorylation or Warburg effect 31 . This is explained by exposure to microenvironments with oxidative stress 18 .…”
Section: Discussionmentioning
confidence: 99%
“…As for VOC analyses using cell lines, five studies were identified based on in vitro experimentation on cell lines and malignant breast tissue biopsy. Four studies used the MCF-7 cell line [16][17][18][19] , two studies used MDA-MB-231 cells [17][18][19] , and one study used malignant breast tissue biopsies 20 . As a result, 72 VOCs, mostly grouped into alcohols, ketones, alkanes, and aldehydes, were obtained (Fig.…”
Section: In Vitro Evidence That Cell Lines "Exhale" Vocsmentioning
confidence: 99%
“…Identification of characteristic compounds of moderate volatility in breast cancer cell lines Tanaka et al 68 Breast cancer…”
Section: Culture Mediamentioning
confidence: 99%